Analisis Efektivitas Pemanfaatan Aplikasi Layanan Kesehatan Mobile Jaminan Kesehatan Nasional Di Indonesia - Hilda Yuliastuti; Moh. Jawahir (Jurnal Pengabdian Kepada Masyarakat (JPKM) Langit Biru, 2023)
The mandatory launch of JKN Mobile in Indonesia was carried out on a digital basis in order to achieve health’s services in the era of technology modernization which is assumed to be able to effectively attract the public as users as well as JKN BPJS & KIS membership at the Indonesia, it is important to conduct research to measure the effectiveness of contribution financing and the number of JKN membership mobile’s, the purpose of this study is to analyze the effectiveness of users of the benefits of the JKN Mobile’s application in Indonesia, the research method uses qualitative with a literature review approach, namely the reporting profile’s of the Ministry of Health in 2021 with analysis of the contents of related journals and book’s, secondary data using systematic interpretation and five social media twitter account’s , the was results of the study show that the JKN Mobile digital-based public health service application satisfies health service users so that it has increased the use of JKN Mobile in the very good category. And it is proven that the effectiveness of users utilizing mobile JKN health services in Indonesia has met the effectiveness of the very good category in early 2021.